Participação e a governança nas organizações mutuais - Alves, Atila Indalecio Marques (2010)
The mutual organizations, whether NGOs, cooperatives, associations, pension funds and clubs among others, are responsible for huge financial, social, and political transactions, however, the governance of such institutions depends greatly on the involvement and effective participation of its participants. This study aims to identify what and how behave the mechanisms of participation in the governance of mutual organizations, compared to the nature of organizations. Initially, presents a review of the concepts of governance, mutual organizations, participation and collective action. Then, based on the approach to social norms proposed by Elster (1989), analyzes the influence of the nature of three mutual organizations facing the norms of cooperation practiced by its components, allowing to identify that, according to the profile of incorporation of the organization, rules of cooperation for the participation in governance may be different and closely related to the cooperative profile of its participants.